Oportunidades y potencialidades en la relación bilateral Ecuador-Panamá - Montesinos, María Dolores (2014)
Within the field of international relations, the opportunities that Latin American countries have, in order to achieve the regional integration are wide and diverse, for instance: the new scheme of South-South Cooperation (SSC), as well as economic and trade interactions, and collaborative and complementary joint initiatives intra-region. The present research is devoted to the study of the Ecuador-Panama bilateral relationship in the past two years, its characterization and identification of synergies and / or matches in which they can boost their bilateral agenda, thus maximizing the benefits for both nations, framed in theoretical thinking of globalization as an alternative to classical and neoclassical tendencies on the international relations, such as realism, neorealism and neoliberalism.